UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN PKN DENGAN PENDEKATAN KOOPERATIF MODEL NUMBERED HEADS TOGETHER ( NHT) DI KELAS V SD NEGERI 3 KERANGAN PURUN - Adi Adi; Muhammad Akip; Asep Eka Nugraha (Bestari: Jurnal Pendidikan dan Kebudayaan, 2021)
Abstract : This Classroom Action Research Aims To Know Improved Learning Outcomes in Civil Education Subjects Before And After Using The Numbered Heads Together (NHT) Cooperative Approach In Class V Elementary School Public 3 KeranganPurun. This research was conducted in two cycles, each cycle divided into 4 steps, consisting of planning, implementing actions, observing, and reflecting.Through This Research, Researchers Hope To Be Able To Improve Learning Outcomes In Pkn Subjects Before And After Using The Numbered Heads Together (NHT) Model Cooperative Approach In Class V Elementary School Public 3 PurunKerangan. Based on data analysis and discussion that has been done, that "Efforts to Improve Student Learning Outcomes in Civil Education Lessons Using the Numbered Head Together (NHT) Cooperative Approach in Class V of Elementary School Public 3 KeranganPurun".From the analysis results obtained a significant increase from Cycle I and Cycle II, Student learning outcomes in the learning process of Citizenship Education is increasing, because of each cycle the average student learning outcomes have reached the criteria, 47% and 85% have reached the criteria predetermined success. It can be concluded that the cooperative approach of the Numbered Head Together (NHT) model can improve student learning outcomes in class V Elementary School Public 3 KeranganPurun.  Keywords: Improving Learning Outcomes, Civil Education and Cooperative Approach Model Numbered Heads Together (NHT). Abstrak: Penelitian Tindakan Kelas IniBertujuanUntukMengetahuiPeningkatan Hasil Belajar Pada Mata Pelajaran PKN Sebelum Dan SesudahmenggunakanPendekatanKooperatif  Model Numbered Heads  Together ( NHT) Di Kelas V SD Negeri 3 KeranganPurun. Penelitianinidilaksanakandalamduasiklus, setiapsiklusterbagimenjadi 4 langkah, terdiridariperencanaan, pelaksanaantindakan, pengamatan, dan refleksi.MelaluiPenelitianIniPenelitiBerharap Mampu Meningkatkan Hasil Belajar Pada Mata Pelajaran PknSebelum Dan SesudahMenggunakanPendekatanKooperatif  Model Numbered Heads  Together ( NHT) Di Kelas V Sd Negeri 3 KeranganPurun. Berdasarkananalisis data dan pembahasan yang telahdilakukan, bahwa “UpayaMeningkatkan Hasil BelajarSiswa Pada Pelajaran PKN DenganPendekatanKooperatif Model Numbered Head Together (NHT) Di kelas V SD Negeri 3 KeranganPurun”. Dari hasilanalisis yang di perolehpeningkatan yang signifikandariSiklus I dan Siklus II, Hasil belajarsiswadalam proses pembelajaran Pendidikan Kewarganegaraaninisemakinmeningkat, karenadaritiapsiklus rata-rata hasilbelajarsiswatelahmencapaikriteria, 47 % dan 85 % telahmencapaikriteriakeberhasilan yang telahditetapkan.Dapatdisimpulkanbahwadenganpendekatankooperatif model Numbered Head Together (NHT) dapatmeningkatkanhasilbelajarsiswa  di kelas V SDN 3 KeranganPurun.Kata Kunci:Meningkatkan Hasil Belajar, PKN dan PendekatanKooperatif  Model Numbered Heads  Together ( NHT).